Linguocultural Analysis of Phraseological Units Expressing Character in English and Uzbek Languages (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
This article shows the analysis of phraseology expressing character in English and Uzbek languages from a linguistic and cultural point of view. Phraseologisms in each language have their own meaning from a national cultural point of view. It is difficult to translate without knowing the culture of the two peoples in order to understand them and feel the color. This article compares English and Uzbek character phrases from a linguistic and cultural point of view.